The high temperature behavior of In2O3 - Wit, J.H.W. de (Elsevier, 1975)
The electrical conductivity of In2O3 has been measured up to 1400°C in air. The temperature dependence of the conductivity at high temperatures yields an activation energy of 1.5 ± 0.1 eV. This activation energy is interpreted in terms of a nonstoichiometric decomposition of the compound. This interpretation is sustained by thermogravimetric analysis in combination with a gas mass analyser. Hall experiments
Keywords: Scheikunde